Understanding the Role of Spatial Configuration on Social Behavior in Educational Buildings - Mine Tunçok Sarıberberoğlu; Alper Ünlü (Iconarp International Journal of Architecture and Planning)
Educational buildings, which appear as a design problem when viewed through the historical process, appear as a whole of structures consisting of educational units of different functions and sizes, shaped through a main corridor space and attached to this main space. On the other hand, when educational buildings are considered through their plan schemes or spatial layouts, it is possible to say that they positively or negatively affect different but interrelated parameters such as students' potential to come together, their motivation in crowds, and their involvement with each other in social relations. In the space syntax theory, buildings are separated from each other in terms of programming; that behavior is shaped and determined by the configuration (strong programming) or possible new forms of behavioral patterns occurring against the layout (weak programming). This study uses a comparative methodology to investigate the effect of the spatial layout of educational buildings on how social interaction is generated and motivated in the relations of 'syntactic programs' in school settings. The study focuses on recess time behavior in relation to the spatial layout and uses behavior maps and space syntax methods to examine the effects of the spatial setups programming parameters in educational buildings. Results show that if an educational building has a flexible structure (weak programming) with its spatial organization, socialization is oriented naturally by the layout with enriched behavioral patterns. However, when the design starts to behave strongly programmed, social behavior becomes monotonous and prevented. As a result, this study shows the importance of understanding social logic in the architectural design of educational buildings in structuring social relationships. Revealing the relationships between these concepts is thought to guide the evaluation of the design criteria of educational buildings and the contents presented for new designs.